Implementation of the Use of Instagram @gramatika_arab in Developing Arabic Language Skills for Students of Arabic Language Education of UIN Sunan Kalijaga - Lu'luun Nisai; Mohamed Ahmed Mohamed Ibrahim Shalgham (Uktub)
Instagram is one of social media equipped with various features and used as a medium of information and communication. One of its functions is to make it easier for Arabic learners to access Instagram accounts that provide several audio-visual-based Arabic content. This research is a qualitative content analysis with Instagram @gramatika_arab as the subject. Data sources in this study consist of primary data sourced from Instagram @gramatika_arab and secondary data in the form of several scientific journals relevant to this study. The data collection method used is the documentation method while data analysis is carried out during the research. The results showed that Instagram @gramatika_arab become one of the accounts providing audio-visual based Arabic content that is widely accessed by Arabic language learners, especially for students of state islamic universities in Indonesia. It is even accessed by several other countries such as Malaysia, Thailand, and Morocco. Content in the form of Arabic quizzes, pamphlets, and handwriting can attract and facilitate Arabic learners in understanding the material. In addition, Arabic language learners can easily access these contents anytime and anywhere.